Industrial Processing Companies in the Moldovan Agri-Food Sector: A Case Study - Alexandru GHENCEA; Silvius STANCIU (Communications of International Proceedings, 2024)
This case study explores the evolution of the food industry's industrial value in the Republic of Moldova, focusing on the role of small and medium-sized enterprises (SMEs) and their impact on the national economy. The study examines the competitive landscape, revenue growth, and key sectors within the agri-food industry, utilizing a variety of data sources including national statistics, economic reports, and relevant legislation. The analysis reveals significant growth in both the number and revenue of SMEs in the food industry, highlighting the sector's contribution to economic development and market competitiveness. Key findings indicate substantial revenue increases in sectors such as vegetable/animal oils and fats, meat processing, and dairy products. The study concludes that the agri-food sector is crucial for Moldova’s economic progress, advocating for continued support and innovation to maintain growth and competitiveness in both domestic and international markets.
Keywords: Enterprises; Competition; Food industry; Republic of Moldova.